Meet Joe Black [videorecording (DVD)] - Brest, Martin, 1951-; Brest, Martin, 1951-; Pitt, Brad, 1963-; Hopkins, Anthony, 1937-; Forlani, Claire; Weber, Jake, 1964-; Harden, Marcia Gay; Casella, Alberto, 1891-1957; Anderson, Maxwell, 1888-1959 (Universal, 1999)
Death appears to claim a wealthy media mogul who bargains for more time, during which Death falls in love with the man's daughter.